2013
DOI: 10.1007/s00535-013-0846-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in patients with cholelithiasis and after cholecystectomy: a nationwide cohort study

Abstract: Cholelithiasis patients have a higher risk of gastrointestinal cancer, particularly of gallbladder and extrahepatic bile duct cancer. Post-cholecystectomy patients have a risk of colorectal and stomach cancer within the first 5 years and persisting after 5 years, respectively. This paper proposes strategies for preventing gastrointestinal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
76
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 30 publications
8
76
1
5
Order By: Relevance
“…[25][26][27] Many population-based studies have demonstrated positive correlations between cholelithiasis or postcholecystectomy status and the risk of biliary tract cancers. 2,7,21 In our study, we demonstrated a higher risk of extrahepatic biliary tract cancer in patients with cholecystitis. Moreover, the HR was still increased after adjusting for associated risk factors.…”
Section: Specific Cancer Typesmentioning
confidence: 68%
See 2 more Smart Citations
“…[25][26][27] Many population-based studies have demonstrated positive correlations between cholelithiasis or postcholecystectomy status and the risk of biliary tract cancers. 2,7,21 In our study, we demonstrated a higher risk of extrahepatic biliary tract cancer in patients with cholecystitis. Moreover, the HR was still increased after adjusting for associated risk factors.…”
Section: Specific Cancer Typesmentioning
confidence: 68%
“…3,8,36 The status post cholecystectomy was also related to hepatic cancer, colorectal cancer, and gastric cancer. 2,3,21,37,38 However, there are few studies that focused on cancer risks in cholecystitis. While our study showed increased SIRs for hepatic cancer, pancreatic cancer, and colorectal cancer in patients with cholecystitis, the adjusted HR for these specific cancers did not remain significant after adjusting for associated risk factors, such as gallstones or cholecystectomy for pancreatic and colorectal cancer, and cirrhosis for liver cancer.…”
Section: Specific Cancer Typesmentioning
confidence: 97%
See 1 more Smart Citation
“…1,2 More recently, clinically diagnosed gallstone disease, including symptomatic gallstones or cholecystectomy, has been explored in cohort studies and associated with higher overall occurrence of cancer, 3,4 with gastrointestinal cancers such as hepatic, 5 biliary, [6][7][8] pancreatic, 4,9 esophageal, 10,11 gastric, 8,12 small intestines, 4,13,14 colon, 4,8,[13][14][15][16][17][18][19] and with nongastrointestinal cancers, such as breast 4,20 and prostate. 21 However, these studies may be biased by the increased risk of cancer detection after clinically diagnosed gallstone disease.…”
mentioning
confidence: 99%
“…Bowel perforations, bile duct injuries, and wound infection increase the morbidity and mortality risks of this procedure [21,22]. Furthermore, GSD after cholecystectomy may be associated with an increased risk of cancers [23,24], including pancreatic cancer [25], liver cancer [26], and colorectal cancer [27]. Biliary juice of patients who received cholecystectomy is secreted into the duodenum continuously, potentially increasing duodenogastric bile reflux [28], and consequently increasing the risk of gastric cancer [29].…”
Section: Introductionmentioning
confidence: 99%